2009
DOI: 10.5004/dwt.2009.703
|View full text |Cite
|
Sign up to set email alerts
|

Cost savings by novel seawater reverse osmosis elements and design concepts

Abstract: Desalination market growth has triggered significant development in SWRO membrane and process development and the new extra high rejection and ultra low energy membranes from Dow, FILMTEC™ SW30XHR-400i and SW30ULE-400i, as well as the internally staged design concept, have been validated in extensive field testing and various commercial plants over the recent years and are now commercially available. These solutions from Dow can be used to increase membrane flux and system recovery and / or to reduce feed pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…They offer high salts rejection, lowenergy requirement and high-productivity up to 47.5 m 3 /d [157][158][159]. Hybrid RO membrane interstage design also called internally staged design is introduced in which different membranes are packed in same pressure vessel to get operational and maintenance advantages and 5% to 8% of capital costs savings as reported by the manufactures [160][161][162][163][164][165].…”
Section: Swro Processesmentioning
confidence: 99%
“…They offer high salts rejection, lowenergy requirement and high-productivity up to 47.5 m 3 /d [157][158][159]. Hybrid RO membrane interstage design also called internally staged design is introduced in which different membranes are packed in same pressure vessel to get operational and maintenance advantages and 5% to 8% of capital costs savings as reported by the manufactures [160][161][162][163][164][165].…”
Section: Swro Processesmentioning
confidence: 99%
“…This system involves the use of low-flux membranes in the front and high-flux membranes in the rear elements [50,51]. This system allows a significant reduction in permeate costs by requiring fewer pressure vessels and fewer membranes [52,53]. Figure 5 illustrates the proposed scheme.…”
Section: Ro Optimization Modelingmentioning
confidence: 99%
“…ISD involves using lower flux membranes at the front and high flux membranes in subsequent elements (Figure 18) [102,103]. It has been shown that such a hybrid membrane inter-stage design has the potential for significant reductions in permeate costs by requiring fewer pressure vessels and membranes [104,105]. This section covers optimization of ISD and other such developments in RO membrane configurations using modelling and simulation over the last 5 years.…”
Section: Optimization Modelling In Romentioning
confidence: 99%